The Influence of Perceived Organizational Support and Trust in Supervisor on Organizational Citizenship Behavior with Job Satisfaction as a Mediating Variable - Erik Ferdiyan Kurnia Harun; Nurul Hermina (Dinasti Publisher, 2025)
This study aims to analyze the effect of perceived organizational support and trust in supervisors on organizational citizenship behavior (OCB), with job satisfaction as a mediating variable. The population in this study consists of permanent employees at PT PLN (Persero) UP3 Cimahi. A purposive sampling technique was employed. The research method used is quantitative with a descriptive-verificative approach. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). A total of 115 respondents were selected using a purposive sampling technique. The results show that perceived organizational support and trust in supervisors have a positive and significant effect on job satisfaction. Furthermore, job satisfaction has a significant effect on OCB and acts as a significant mediating variable in the relationship between perceived organizational support and trust in supervisors on OCB. These findings imply that strengthening organizational support and trust-based leader-subordinate relationships can enhance employees’ extra-role contributions to the organization.